Deconstructing the substantialist conception of God: recasting Heidegger's critique of Augustine - de Oliveira, Nythamar (Veritas (Porto Alegre), 2017)
In this paper, I argue that Augustine's conception of God as substance (substantia) has misleadingly been evoked by Martin Heidegger's deconstruction of onto-theological and substantialist variants of metaphysics as they mistook entities (Seienden, entia, beings) for their very Being (Sein, ens, esse) which cannot be conceptualized or objectified by human thinking, but makes both their thought and reality possible. Even though Augustine sought somehow to reconcile a Neoplatonic, essentialist cosmology with a Judeo-Christian worldview of historical redemption, Heidegger not only failed to properly recognize his indebtedness to Augustinian existential anthropology, but also the latter's contention that the actuality of beings and contingent history ultimately determines ontological concepts in their basic difference from their ontical counterparts, compromising thus Heidegger's intuitive criticisms against the confusion between God and Being (Sein).